Historical Foundations of the Person-Oriented Approach (Journal of Pedagogical Inventions and Practices, 2023)
The article discusses the historical foundations of the person-oriented approach and the works of scholars who contributed to its development. Basically, the role and importance of the person-oriented approach in the works of our great ancestors, foreign and national scientists has been highlighted.